Clay and heavy minerals and total organic carbon in Arctic Ocean surface sediments – Data tables to distribution maps of Stein (2008) - Stein, Ruediger (PANGAEA, 2026)
Total organic carbon (TOC) and mineral assemblages are key data sets determined to characterize marine sediments in terms of sediment provenances, processes, and depositional environments. In a comprehensive review and synthesis (Stein, 2008), such data were compiled for Arctic Ocean surface sediments and shown in nine selected distribution maps: four maps of clay minerals (illite, smectite, chlorite, and kaolinite), four maps of heavy minerals (amphibole, clinopyroxene, epidote, and garnet), and one TOC map. The data used to produce these maps, are represented in the three tables of this data report. For details in background information and methodology see primary source literature cited here as well as the Stein (2008) synthesis.
Keywords: Arctic Ocean; Clay minerals; heavy minerals; Surface sediments; Total organic carbon (TOC)